Youth entrepreneurship in agribusiness: Bangladesh country report - Babu, Suresh Chandra; Zhou, Yuan; Khan, Reza; Srivastava, Nandita (Syngenta Foundation, 2021)
Youth entrepreneurship is identified as an important pathway to harness the demographic dividend. It provides a means for growth and productive employment in developing nations. The agriculture sector in developing countries like Bangladesh has the potential to create opportunities for youth entrepreneurship, but certain key challenges can constrain progress. These challenges include lack of skills training support and poor access to credit, infrastructure, technology, and markets. To address these concerns, a first step is to recognize factors that contribute to the success of youth entrepreneurs (YEs), identify key stakeholders who can create and support entrepreneurial opportunities, and design ways to expand the scale of existing YEs. This report is part of an international multi-country comparative study on youth entrepreneurship in agribusiness. It uses a conceptual framework on key drivers of the success of youth entrepreneurship. It provides a literature review of the status of the policy, institutional, technological, business, and individual environments that support youth entrepreneurship in Bangladesh. A case study approach is used to understand the support and constraints faced by existing rural and urban YEs. Using the insights from the literature and case studies, key lessons and recommendations are provided to strengthen youth entrepreneurship in the agriculture sector in Bangladesh.